The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2478/msp-2022-0042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the properties of cast asphalt concrete mixture with the addition of fiber from the fly ash of thermal power plants

Abstract: The introduction of new road-building materials with advanced physical and mechanical properties is the trend in contemporary civil engineering, which aims to increase the quality of road surfaces. The use of cast asphalt concrete in the upper layers of road surfaces as a replacement for layers made of traditional fine-grained asphalt concrete will not only increase the pace of construction and repair, but also the durability and quality of the road pavement. However, this method requires operational and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These effects were observed by (Boukhari et al, 2015) which recommended the addition content between 2% to 8%. Furthermore, the optimal amount of fiber from fly ash in cast hot asphalt concrete is 4.0% of the mass (Bieliatynskyi et al, 2022) and 10wt% with waste plastic bags (Kowanou, 2014). The incorporation of glass particles at 10wt% in the mixtures increase the performance of bituminous coating of type ESG10 and GB20 (Bachand, 2018).…”
Section: Samples Of Asphalt Oncretementioning
confidence: 99%
See 2 more Smart Citations
“…These effects were observed by (Boukhari et al, 2015) which recommended the addition content between 2% to 8%. Furthermore, the optimal amount of fiber from fly ash in cast hot asphalt concrete is 4.0% of the mass (Bieliatynskyi et al, 2022) and 10wt% with waste plastic bags (Kowanou, 2014). The incorporation of glass particles at 10wt% in the mixtures increase the performance of bituminous coating of type ESG10 and GB20 (Bachand, 2018).…”
Section: Samples Of Asphalt Oncretementioning
confidence: 99%
“…As a result, there is a huge proliferation of this plastic waste, leading to environmental problems given its nonbiodegradable nature. The introduction of new road-building materials with advanced physical and mechanical properties is the trend in contemporary civil engineering, which aims to increase the quality of road surfaces (Bieliatynskyi et al, 2022) and safety (St-Jacques et al, 2009). According to previous research work, the mixtures modified with recycled-plastic additives (Russo et al, 2022;Pugin et al, 2022), the addition of fiber from the fly ash of thermal power plants (Bieliatynskyi et al, 2022), the glass particle, showed higher stiffness and tenacity and as expected though, with specified physical, mechanical and operational properties in line with the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, based on the material's characteristics, gussasphalt concrete was improved and defined as mastic asphalt concrete. The mastic asphalt concrete production process is complex, requiring adding asphalt and aggregate in batches, then mixing for up to 6 h, and finally paving and forming with a special paver [1,2]. In the long-term mixing process, the viscosity of mastic asphalt concrete gradually decreases with the increase in mixing time.…”
Section: Introductionmentioning
confidence: 99%